Cergas Subuh Enterprise: nurturing Islamic principles and ethnic values - Mhd. Sarif, Suhaimi; Ismail, Yusof; Yahya, Rohaziah (IIUM Press, 2023)
Embark on a captivating exploration into the remarkable odyssey of Cergas Subuh Enterprise, an extraordinary small business nestled in the heart of Ulu Gombak, Selangor. Firmly grounded in the tenets of Islamic values and deeply rooted in the vibrant Minang ethnic culture, this humble enterprise showcases an awe-inspiring journey of resilience and determination. Witness the remarkable devotion with which they navigate the ever-evolving challenges brought about by rapid urbanization. Despite the encroachment of concrete jungles and the allure of modern amenities, they remain resolute in preserving their ancestral ties to the land. While upholding their treasured traditions, they skill-fully merge the wisdom of the past with the innovations of the present. Furthermore, in an era dominated by the digital age, Cergas Subuh Enterprise fearlessly embraces technology, leveraging its power to expand their reach and connect with a broader customer base. By effectively harnessing the potential of online platforms and social media, they ingeniously showcase their produce while preserving the authentic essence of their Minang heritage. Intriguingly, this case serves as a profound reminder that tradition and progress can harmoniously coexist.